1996
DOI: 10.1111/j.1476-5381.1996.tb15747.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by vitamin E of drug accumulation and of phospholipidosis induced by desipramine and other cationic amphophilic drugs in human cultured cells

Abstract: 1 Cationic amphiphilic drugs (CADs) are widely used in chronic pharmacotherapies in spite of frequently observed side effects connected with lysosomal phospholipid (PL) storage. 2 It has recently been shown that cx-tocopherol (a-Toc) inhibits drug-and PL accumulation in cell cultures chronically exposed to the CAD, amiodarone. 3 The mechanisms of a-Toc action on drug kinetics and PL storage were studied in human cultured fibroblasts exposed to single and repetitive doses of desipramine and other CADs. 4 a-Toc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Of these CADs, CPZ exhibited the greatest uptake with respect to phospholipid interactions, whereas the largest interactions were observed for bilayers comprising DOPC. Previous studies have also demonstrated CPZ to have a greater interaction and thus uptake relative to AMI and PROP, [6,7,[10][11][12] presumably as CPZ is more hydrophobic. [12] Importantly, however, the boundaries of previous work have been extended, as two discrete binding processes were identified.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of these CADs, CPZ exhibited the greatest uptake with respect to phospholipid interactions, whereas the largest interactions were observed for bilayers comprising DOPC. Previous studies have also demonstrated CPZ to have a greater interaction and thus uptake relative to AMI and PROP, [6,7,[10][11][12] presumably as CPZ is more hydrophobic. [12] Importantly, however, the boundaries of previous work have been extended, as two discrete binding processes were identified.…”
Section: Discussionmentioning
confidence: 96%
“…[19] This results in the formation of thread-like micelles, and finally formation of spherical micelles after approximately two hours. [19] It is postulated herein that the second process represents intercalation of each drug to form a drug-phospholipid complex, [11,20] www.chemmedchem.org as drugs did not dissociate completely from the membrane as evidenced by the residual response in SPR following exposure to the drug. Earlier studies have also attributed further intracellular accumulation of drugs with these drug-phospholipid complexes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Electron cryo-microscopy studies have also proposed that a drug from the same family as CPZ disrupts the bilayer by perturbation of the local organisation of phospholipids [21]. In the current study, it also postulated that the second process represents intercalation of each drug, forming a drug/phospholipid complex [22,23] as drugs did not dissociate completely from the membrane as evidenced by the residual response in SPR following exposure to the drug. It has been proposed that formation of drug/phospholipid complexes mimics phospholipidosis [14,19,23], a type of lipid storage disorder [24] which could give rise to the observed defects.…”
Section: 11nmmentioning
confidence: 73%
“…In vitro studies performed by Scuntaro et al (1996) showed that PL-CAD accumulation can be potentially inhibited by D-a-tocopherol (vitamin E). This research suggested that competition between vitamin E and drug for cell membranes prevented the formation of phospholipid-drug complexes.…”
Section: Introductionmentioning
confidence: 99%